KEABSAHAN LELANG EKSEKUSI HAK TANGGUNGAN KARENA ADANYA GUGATAN DARI DEBITOR - Muhammad Zainal Abidin, 031514253022 (2018)
Credit is one of the banking services to customers that is realized in a credit agreement by providing a number of debt with repayment in the agreed time period. In the credit agreement, the bank will ask for a guarantee, and one type of the guarantee is land mortgage. Since the enactment of Law Number 4 of 1996 concerning Land Mortgage, mortgage holders can execute objects on regarding land mortgage without prior approval from the debtor (Parate Executie) and without requiring fiat court, namely by selling through auction, thus this makes it easy for the mortgage holders to obtain repayment of their receivables. However, in practice, they often encounter obstacles in the execution regarding parate executie procedure on the Article 6 of the Land Mortgage Law if there is a lawsuit from the debtor that impedes the auction process, or, when emptying the auction object where the auction winner has been determined and the auction minutes have been issued. The lawsuit is based on an unlawful act (tort) because it considers the auction process invalid, or the limit value is too low, and various other reasons.